Rectification and barrier height inhomogeneous in Rhodamine B based organic Schottky diode - Farag, A. A. M.; Yahia, I. S. (Elsevier Science Sa, 2011)
Thermogravimetric analysis (TGA) and X-ray diffraction (XRD) were used to study the structure characterization of the Rhodamine B (Rh.B). The thermal stability and the lattice parameters were calculated using TGA and XRD, respectively. Bulk Al/Rh.B Schottky barrier device was prepared and their properties have been investigated by current density-voltage J-V and capacitance-voltage C-V characteristics in the temperature range 300-400 K. The device parameters extracted from the J-V and C-V characteristics are strongly influenced by the effect of temperature. The device exhibits a strong rectification characteristic and shows a maximum rectification ratio at approximate to 0.15 V for all the studied temperature range. The results clearly demonstrate that the electron transport at the Al/Rh.B interface is significantly affected by low barrier patches. The discrepancy between Schottky barrier heights (SBHs) obtained from the temperature dependencies of both J-V and C-V measurements is explained by the introduction of a spatial distribution of BHs due to the barrier height inhomogeneities that prevail at the Al/Rh.B interface. The deviations of apparent BHs were investigated by considering the microstructure of the Al/Rh.B interface. Moreover, the distribution of carrier concentration through the width of the depletion region is nearly uniform. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Organic Schottky diode; Rhodamine B; Schottky diode; Current-voltage; Capacitance-voltage; Barrier height inhomogeneity